Density-dependent changes in the distribution of Southern Right Whales (Eubalaena australis) in the breeding ground Peninsula Valdés - Sueyro, Nicolás; Crespo, Enrique Alberto; Arias, Magdalena; Coscarella, Mariano Alberto (PeerJ)
Background: The Southern Right Whale (Eubalaena australis) population of the South–western Atlantic Ocean is recovering. In the breeding ground of Peninsula Valdés, as a consequence of the population growth, expansion to new areas by some types of groups and a change in the habitat use patterns at the coastal area were recorded. Methods: We analysed information gathered from aerial surveys conducted along the coast of Peninsula Valdés in 15 years of effective sampling in a 19-year span. These surveys were divided into four periods (1999–2000; 2004–2007; 2008–2012 and 2013–2016) and estimated the density of whales in a 620 km of coast divided into segments of five km. Results: The density of the whales increased to near three whales per km2 (averaged over each period) in the high-density areas. When this mean number was reached, the significant changes in density in the adjacent areas were detected in the following period. These changes were a decrease in density in the high-density areas and an increase of density in the low-density areas. Discussion: We propose that a threshold in density elicits a response in habitat use, with the Mother-calf pairs remaining in the area, while the other groups are displaced to new areas. Fil: Sueyro, Nicolás. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Centro para el Estudio de Sistemas Marinos; Argentina. Universidad Nacional de la Patagonia "San Juan Bosco"; Argentina Fil: Crespo, Enrique Alberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Centro para el Estudio de Sistemas Marinos; Argentina. Universidad Nacional de la Patagonia "San Juan Bosco"; Argentina Fil: Arias, Magdalena. Universidad Nacional del Comahue. Instituto de Biología Marina y Pesquera Almirante Storni; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional ...